Impact of climatic change on water resources in Huia river basin, China - Othman Alia, Rawshan; Chunjua, Zhao; Yihona, Zhou; Ping, Liu; Heryansyaha, Arien; Nawaz, Nadeem (International Journal of Engineering and Technology, 2018)
Research on the impact of climate change on water resources has attracted the attention of academician and policy makers. This paper tends to analyze the impact of changes in air temperature and rainfall factors on the amount of water resources in the Huai River Basin from 1980 to 2014. Air temperature and rainfall data were collected from six meteorological stations. Hydrological and water resources evaluation data were collected from the Bengbu Hydrological Station in the Huai River Basin. Research findings revealed an increasing trend of average annual air temperature, with the highest increase of 0.293oC recorded at Bengbu in Anhui Province. The western part of the study area has shown a rising rainfall while the eastern part (the middle reaches of the Huai River) witnessed a declining rainfall. The rainfall in the Huai River Basin was significantly influenced by the natural fluctuations as the average rainfall in the study area was in a vaguely declining trend. This resulted in gradual decrease in the quantity of the Basinâ€™s water resources due to decreasing rainfall and rising air temperature. Regression and sensitivity analyses were employed to develop a mathematical model between water resources quantity and changes in air temperature and rainfall. Based on regression analysis findings, changes in rainfall have a much bigger impact on its water resources quantity than changes in its air temperature.Â Â
Keywords: Climate Change; Rainfall; Air Temperature; Water Resources; Huai River; and Sensitivity and Regression Analysis.